«Veritatem diligere». Mission of the University: To search, to find, to communicate truth - Abellán-García Barrio, Álvaro; Agejas Esteban, José Ángel; Antuñano Alea, Salvador (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
Although it should be evident, the necessary relation between University and Truth is frequently obscured by the relativistic tendencies of our times and by the primacy of the practical and the useful. Against this background, and in order to rediscover and measure the importance of Truth as the essential mission of the University, the present article intends, first, to describe the contemporary cultural circumstances in relation to Truth; and, second, to explore a sense of Truth within the order of love —and not only within the order of thought. Finally, the article shows the reason why the University can only be such in the very measure that it is devoted to searching, finding and communicating Truth, from within the tension and the impetus that come precisley from the order of love.